Imperfect Competition and the Resource Allocative Effects of Effective Protection: Comment - Dutton, John; Tower, Edward (Review of Economic Studies, 1979)
John Dutton, Edward Tower; Imperfect Competition and the Resource Allocative Effects of Effective Protection: Comment, The Review of Economic Studies, Volu